Determinasi Pertumbuhan Laba Berdasakan Rasio Keuangan Pada Perusahaan Pertambangan Yang Terdatar Di Bursa Efek Indonesia - Nur Sayidatul Muntiah; Nurul Hidayah; Arif Hartono (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to determine the determination of profit growth based on financial ratios proxied by the Quick Ratio, Debt to Equity Ratio, Total Asset Turnover and Net Profit Margin in mining companies listed on the Indonesian stock exchange. This study uses a quantitative approach. The data source comes from secondary data , namely the annual financial reports of mining companies downloaded from the website www.idx.co.id. The population in this study are all mining companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The technique of taking samples using purposive sampling technique. The criteria for sampling are a: mining companies that publish consecutive annual financial reports during the 2019-2021 period and b: mining companies that experience profits during the 2019-2021 period. The data analysis method in this study uses the classical assumption test, multiple linear regression analysis, t test, f test and determination test. The results of data analysis show that the data is free from classical assumptions. Quick Ratio variable partially has no effect on profit growth, Debt to Equity Ratio variable partially has no effect on profit growth, Total Asset Turnover partially affects profit growth, and Net Profit Margin partially affects profit growth . The simultaneous influence of the variables Quick Ratio, Debt to Equity Ratio, Total Asset Turnover and Net Profit Margin has a positive and significant effect. Keywords : Quick Ratio; Debt to Equity Ratio; Total Asset Turnover; Net profit Margins; Profit Growth